Matched comparison of 3 cerebral perfusion strategies in open zone-0 anastomosis for acute type A aortic dissection. (9th April 2022) - Montagner, Matteo; Kofler, Markus; Pitts, Leonard; Heck, Roland; Buz, Semih; Kurz, Stephan; Falk, Volkmar; Kempfert, Jörg
Abstract: OBJECTIVES: The present study aims to investigate outcomes after the surgical treatment of acute type A aortic dissection in regard to three available selective cerebral perfusion strategies. METHODS: From 2000 to 2019, patients were selected based on the employment of either retrograde cerebral perfusion (RCP), unilateral antegrade cerebral perfusion (uACP) or bilateral antegrade cerebral perfusion (bACP) during open zone-0 anastomosis. Propensity score TriMatch analysis considering several preoperative and intraoperative variables was used to identify well-balanced triplets. The primary end point of the study was a new cerebral operation-related neurologic deficit. RESULTS: Operative times (operation time, cardiopulmonary bypass time, reperfusion time) were significantly longer in the RCP group, in which deeper hypothermia was applied (27.5 [24–28], 28 [26–28] and 16 [16–17]°C for uACP, bACP and RCP, respectively, P -value <0.001). The RCP group showed higher red blood cell concentrates and fresh frozen plasma transfusion rates. No significant difference of new cerebral operation-related neurologic deficit was observed between the 3 groups (12.9% vs 12.9% vs 11.3% for RCP, uACP and bACP, P -value = 0.86). In addition, 30-day mortality showed similar distribution independently of the cerebral perfusion strategy adopted (17.7% vs 14.5% vs 17.7% for RCP, uACP and bACP, P -value = 0.86). CONCLUSIONS: However, based on a small sample size, the comparison showed no relevant differences in terms of neurologic outcome and 30-day mortality, confirming RCP, uACP and bACP as safe and reproducible selective cerebral perfusion strategies in surgery for acute type A aortic dissection. Abstract : The surgical treatment of acute type A aortic dissection (ATAAD) remains challenging and is still associated with high mortality and morbidity rates, especially in the elderly [1].